The Overlapping Roles of Antimicrobial Peptides and Complement in Recruitment and Activation of Tumor-Associated Inflammatory Cells - Al-Rayahi, Izzat A. M.; Sanyi, Raghad H. H. (Frontiers in Immunology, 2015)
Antimicrobial peptides (AMP) represent a group of small biologically active molecules which can be produced by plants, animals, mammals and microorganisms. They are an important element of the innate immune response and thought to possess antibiotic, antifungal and antiviral potentials. Furthermore, AMP may be involved in a number of other activities such as angiogenesis and modulation of immune response which may include stimulation of chemokines and chemotaxis of leukocytes. Initially, AMP have been studied and proposed as alternative therapies for infectious diseases. However, there have been an increasing number of studies proposing that AMP also have a cytotoxic activity against tumour cells. Further development of the biological function of these peptides during tumour development and progression will aid in the development of new, less harmful antitumour therapies. The tumour microenvironment is characterised by the presence of a complex network of cellular interactions involving both proinflammatory and suppressive cells. Components of the complement system play an important role during inflammation and modulating the innate immune response during infection. In addition, complement plays a role in the immune response to cancer and possibly in the trafficking of cells in the tumour microenvironment. This article will try to outline the cross talk between antimicrobial peptides and complement in mobilisation and recruitment of cells in tumour microenvironment.